STUDENTS’ PERCEPTION ON THE USE OF GOOGLE CLASSROOM IN WRITING ACTIVITIES - Suramto Suramto; Titania Gustiana (Jurnal Perspektif Pendidikan, 2023)
Google Classroom as a learning media is widely used for distant learning during pandemic to help students’ learning in English writing. This research is intended to find out students’ perceptions on the use of Google Classroom in writing activities at Universitas Musi Rawas. The numbers of ten students of Public Administration study program are taken by using maximum variation sampling technique. The qualitative method was used in this research with case study as research design. The data obtained from interviews were analyzed by using thematic analysis. The results of the research showed that there are some advantages and disadvantage of Google Classroom in writing activities. The advantages were (1) Easy to use and accessible from mobile phone, (2) Effective communication and sharing, and (3) Speed up the assignment process. Meanwhile, the disadvantage were (1) Networking problem, and (2) Google Classroom did not encourage the learners to share their work with their peers.